Efficacy and safety of two rituximab biosimilars for treating immune thrombocytopenia: a reference-product matched study. (31st December 2023) - Mageau, Arthur; Bonnotte, Bernard; Ebbo, Mikael; Dossier, Antoine; Galicier, Lionel; Souchaud-Debouverie, Odile; Orvain, Corentin; Gerfaud-Valentin, Mathieu; Gobert, Delphine; Riviere, Etienne; Audia, Sylvain; Mahevas, Matthieu; et al.
Abstract: The emergence of rituximab biosimilars offers the prospect of significant savings to the healthcare system. However, these drugs have never been evaluated for treating immune thrombocytopenia (ITP). This was an observational, matched study. We included adults who received a rituximab biosimilar for ITP. Each rituximab-naïve biosimilar patient was matched with two controls from the historic ITP-ritux registry. For non-naïve patients, we compared the response to the biosimilar with that observed with the reference product. Response status was defined according to international criteria. We included 107 patients; 55 receiving Rixathon™ and 52 Truxima™. Three months after the first infusion of rituximab biosimilars, the overall response rate was 47/74 (63.5%) versus 76/142 (53.5%) for the matched controls receiving the reference product ( p = .13). The 3-month overall response rate was 76.5% for Rixathon™ versus 51.5% for the matched control group ( p = .01) and 21/40 (52.5%) for Truxima™ versus 41/74 (55.4%) for the matched controls ( p = .81). For non-naïve patients, the response pattern was similar to that observed previously with the reference product. Safety was analogous to that observed with the reference product. Rituximab biosimilars seemed safe and effective for ITP treatment. Plain Language Summary: What is the context? Immune thrombocytopenia (ITP) is an autoimmune disease defined by a low platelet count without any other cause of thrombocytopenia. Patients with ITP may experience severe bleedings. Rituximab, a biotechnological therapy, is a valid second-line treatment option for ITP. Biotechnological therapies are expensive. Because the patent expiratory date of the reference product of Rituximab expired, highly similar drugs called biosimilars have been developed and used in ITP treatment without any direct evaluation in this particular disease. What is new? In this study, we evaluate the efficacy and safety of rituximab biosimilars versus the reference product for treating adult ITP We included adults who received a rituximab biosimilar for ITP. Each rituximab-naïve biosimilar patient was matched with two controls from a historic registry that included ITP patients treated by the reference product. For non-naïve patients, we compared the response to the biosimilar with that observed with the reference product. For naïve and non-naïve patients, the response pattern was similar to that observed previously with the reference product. Safety was analogous to that observed with the reference product. What is the impact? This study provides further evidence that rituximab biosimilars are safe and effective for immune thrombocytopenia treatment.